Graphene and poly(ionic liquid) modified polyurethane sponges with enhanced flame‐retardant properties. Issue 44 (20th July 2017) - Wei, Huijuan; Zhu, Zhaoqi; Sun, Hanxue; Mu, Peng; Liang, Weidong; Li, An
ABSTRACT: Graphene (Gr) and poly(ionic liquid) (PIL) modified polyurethane (PU) sponges with enhanced flame‐retardant properties were prepared by the direct dip coating of Gr and ionic liquid (IL) monomers onto a PU sponge followed by the polymerization of IL monomers under thermal initiation. With a content of 1.5% Gr in IL, the limiting oxygen index (LOI) of PU–PIL–Gr was 26.1%, whereas the neat PU sponge showed an LOI of only 17.9%. The horizontal flame test results indicate that PIL–Gr prevented horizontal flame spread and eliminated melt dripping. Compared with that of the neat PU sponge, the peak heat release rate of PU–PIL–Gr decreased about 22.0%. These improvements on flame retardancy might have been due to a hybrid flame retardant originating from Gr (which acted as carbon source) and PIL (which contained the flame‐retardant elements) in the PU sponge and the formation of protective layers, which isolated the oxygen and heat more effectively. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45477. Abstract :